Implementasi Pelaksanaan Ekstrakurikuler Salah Satu SD Swasta Di Kabupaten Bandung - Detania Hidapenta; Rizma Rubia Ningsih; Syahid Musthofa Akhyar; Agus Mulyana (Pusat Riset dan Inovasi Nasional, 2024)
There are many benefits to implementing extracurricular activities in elementary schools, one of which is providing a platform for students to develop their hobbies, talents, and interests. This can be a solution to address the decline in moral values among teenagers as a consequence of the era of globalization and technological advancement. This research employs a qualitative method with interview data collection techniques, involving teachers and school principals from private elementary schools in the Cibiru District, Bandung Regency. The results of the conducted research include: The school implements extracurricular activities outside regular class hours, offering both mandatory and optional programs. Various activities, from arts to sports, cater to diverse student interests. The school aims to instill discipline, nurture character, enhance subject understanding, and boost students' skills. Despite challenges like scheduling conflicts and coach delays, the school proactively addresses them through pre-agreements and external facility rentals. Students enthusiastically participate, viewing extracurricular activities as a reliever from classroom stress.